Case Report: Unusual Aggregation of Different Glomerulopathies in a Family Resolved by Genetic Testing and Reverse Phenotyping - Kumar, Reeti; Keskinyan, Vahakn; Stangl, Megan Chryst; Lane, Brandon M.; Buckley, Anne F.; Barisoni, Laura; Howell, David N.; Gbadegesin, Rasheed A. (Frontiers in Pediatrics, 2022)
Glomerular diseases (GDs) are a major cause of chronic kidney disease in children. The conventional approach to diagnosis of GDs includes clinical evaluation and in most cases kidney biopsy to make a definitive diagnosis. However, in many cases, clinical presentations of different GDs can overlap, leading to uncertainty in diagnosis and management even after renal biopsy. In this report, we identify a family with clinical diagnoses of post infectious glomerulonephritis and IgA nephropathy in a parent and two children. Renal biopsies were initially inconclusive, however genetic testing showed that the two individuals diagnosed at different points with IgA nephropathy carried novel segregating pathogenic variants in COL4A5 gene. We were only able to make the final diagnoses in each of the family members after genetic testing and reverse phenotyping. This case highlights the utility of genetic testing and reverse phenotyping in resolving clinical diagnosis in families with unusual constellations of different glomerulopathies. We propose that clustering of different glomerular disease phenotypes in a family should be an indication for genetic testing followed by reverse phenotyping.